2006
DOI: 10.1007/s00264-005-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament insufficiency: does delay in index surgery affect outcome in recreational athletes

Abstract: The aim of the study was to see if delay in anterior cruciate ligament (ACL) reconstruction affects post-reconstruction outcome in recreational athletes. Sixtytwo recreational athletes who had arthroscopic ACL reconstructions using quadruple hamstring grafts between 1997 and 2000 were retrospectively evaluated. Patients with less than 2 years' follow-up, those with multi-ligament injuries, reconstructions for previous failed repairs, those whose injury date was unknown, those with pre-injury Tegner activity le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…de Roeck and Lang-Stevenson 13 suggested that in the ACL-deficient state, a delay to surgery increases the risk of sustaining a meniscal injury, with 10.3% patients suffering a meniscal tear during the waiting period. Our analysis was unable to detect any influence from a delay to surgery, as seen by Tambe et al 46 Although the relationship between chondral damage at surgery and OA is not as well established as that of meniscal injury, some authors have acknowledged its importance for radiological outcome. 23,31 Other authors have found chondral damage to be related to poor radiological outcome.…”
Section: Associations With Poor Radiographic Outcomecontrasting
confidence: 60%
“…de Roeck and Lang-Stevenson 13 suggested that in the ACL-deficient state, a delay to surgery increases the risk of sustaining a meniscal injury, with 10.3% patients suffering a meniscal tear during the waiting period. Our analysis was unable to detect any influence from a delay to surgery, as seen by Tambe et al 46 Although the relationship between chondral damage at surgery and OA is not as well established as that of meniscal injury, some authors have acknowledged its importance for radiological outcome. 23,31 Other authors have found chondral damage to be related to poor radiological outcome.…”
Section: Associations With Poor Radiographic Outcomecontrasting
confidence: 60%
“…The optimal time for surgery has not been established and remains a contentious issue in the surgery of human beings. Although there is good evidence that delayed surgery results in a greater prevalence of meniscal tears (Keene and others 1993, Millett and others 2002), articular cartilage damage (Smith and others 2002, Nelson and others 2006) and soft‐tissue atrophy, some studies suggest that a delay in the index surgery does not affect the short to medium term functional outcome in most human patients (Tambe and others 2006). However, it is generally accepted that the chondral consequences of delayed surgery can be associated with the progression of osteoarthritis (Nelson and others 2006) and a poorer outcome in the longer term in human patients (Marcacci and others 1995, Magnussen and others 2009,).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple factors which can influence the outcome of ACL reconstruction surgery, including age, sex, duration of an injury, the timing of surgery, pre‐operative Tegner score, size and type of the graft, etc. [7, 8, 12, 32, 34]. However, the type of graft used is still one of the main factors for a successful outcome.…”
Section: Introductionmentioning
confidence: 99%